Burden of disease due to amphetamines, cannabis, cocaine, and opioid use disorders in South America, 1990–2019: a systematic analysis of the Global Burden of Disease Study 2019. (February 2023) - Castaldelli-Maia, João M; Wang, Yuan-Pang; Brunoni, Andre R; Faro, Andre; Guimarães, Rafael A; Lucchetti, Giancarlo; Martorell, Miquel; Moreira, Rafael S; Pacheco-Barrios, Kevin; Rodriguez, Jefferson A B; Roever, Leonardo; Silva, Diego A S; et al.
Summary: Background: South America's substance use profile, poverty, income inequality, and cocaine-supplier role make it a unique place for substance use research. This study investigated the burden of disease attributable to amphetamine use disorder, cannabis use disorder (CAD), cocaine use disorder, and opioid use disorder (OUD) in South America from 1990 to 2019, on the basis of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019. Methods: GBD 2019 estimated the incidence, prevalence, mortality, years of life lost (YLL), years of life lived with disability (YLD), and disability-adjusted life-years (DALYs) due to substance use disorders in each of the 12 South American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Guyana, Paraguay, Peru, Suriname, Uruguay, and Venezuela). Data were modelled using standardised tools (ie, the Cause of Death Ensemble model, spatio-temporal Gaussian process regression, and disease modelling meta-regression) to generate estimates of each quantity of interest by sex, location, and year. The analysis included comparisons by sex and country, and against regional and global estimates. Findings: In 2019, the highest amphetamine use disorder burden per 100 000 population in South America was in Peru (66 DALYs). CAD DALY rates per 100 000 in South America were stable between 1990 and 2019, except in Chile and Colombia, which had the highest rates in 2019 (19 DALYs for Chile and 18 DALYs for Colombia). OUD DALYs per 100 000 increased during the period in Brazil and Peru, which in 2019 had the highest rates in South America (82 DALYs for Brazil and 70 DALYs for Peru). In 2019, Brazil had the highest cocaine use disorder DALYs per 100 000 (45 DALYs), nearly double its rate in 1990. DALY rates were higher in males than females for each substance use disorder, except in Paraguay. The overall burden of substance use disorders was higher in males than in females, mainly because of cocaine use disorder and CAD, whereas for amphetamine use disorder, the difference between sexes was minimal, and for OUD there was no difference. For males and females, the highest rate of substance use disorders DALYs per 100 000 was for OUD except in Argentina (in males, 58 DALYs for cocaine use disorder vs 52 DALYs for OUD) and in Paraguay (in females, 77 for amphetamine use disorder vs 50 for OUD). CAD DALY rates were generally the lowest among the substance use disorders for males and females. Amphetamine use disorder YLD rates were reasonably stable throughout the period and were highest in Peru, Paraguay, and Uruguay (>40 YLD per 100 000). For CAD, YLD rates were stable in all countries except Chile and Colombia. Cocaine use disorder YLD rates per 100 000 for the top four countries (Argentina, Uruguay, Chile, and Brazil) increased from 1990 to 2010 (eg, from 19 to 33 in Brazil), but decreased between 2010 and 2019 (eg, from 36 to 31 in Chile). For OUD, YLD rates showed a slight increase in most countries apart from Brazil, which increased from 52 in 1990 to 80 in 2019 and was top among the countries. Amphetamine use disorder YLL rates per 100 000 were highest in Suriname and Peru during the period, although in Suriname it increased from 2·7 in 2010 to 3·2 in 2019, whereas in Peru it decreased from 2·1 to 1·7. The highest YLL rate for cocaine use disorder was in Brazil, which increased from 3·7 in 1990 to 18·1 in 2019. Between 2000 and 2019, Chile and Uruguay showed the highest OUD YLL rates (11·6 for Chile and 10·9 for Uruguay). A high incidence of CAD was found in Chile, Colombia, Guyana, and Suriname. There were high incidences of amphetamine use disorder in Paraguay, cocaine use disorder in Argentina, and OUD in Ecuador. A decrease in annual prevalence for substance use disorders during the period was observed in Venezuela (amphetamine use disorder, CAD, and OUD), Brazil (CAD and amphetamine use disorder), Colombia (amphetamine use disorder and cocaine use disorder), Peru (amphetamine use disorder and cocaine use disorder), Chile and Suriname (amphetamine use disorder), Uruguay (CAD), and Bolivia (OUD). Overall, the cocaine use disorder burden stabilised then decreased. OUD was less prevalent than other substance use disorders but its burden was the highest. Interpretation: The decrease in the burden of cocaine use disorder probably reflects the success of national standardised treatment programmes. Programmes for amphetamine use disorder, CAD, and OUD management should be improved. We did not find an increase in CAD burden in Uruguay, the country with the highest degree of cannabis decriminalisation in the region. Countries in South America should improve monitoring of substance use disorders, including regular surveys to provide more accurate data on which to base policy decisions. Funding: The Bill & Melinda Gates Foundation.